Association between Oral Error Corrections of University Teacher and English Majors’ Language Anxiety in Philippine Higher Education Context - Guibangguibang, Herford Rei Biscayno (International Journal of Language Education, 2020)
This study sought to answer the question on the level of English language anxiety in the ESL and mainstream classrooms of 61 total number of English major students utilizing the 20-item self-assessment questionnaire of English Language Anxiety Scale (ELAS) developed by Pappamihiel (2002). Actual one-hour footage of classroom was documented through a MONACORR audio-recorder, thrice with each teacher. The recorder was given to one of the teachers’ students without knowledge for the authenticity of their oral corrections. After having identified the existing oral error corrections by the English teachers through audio-recording, a self-made questionnaire was answered by the students to find what is the rate of occurrence of the identified oral error correction styles. The frequency count, weighted mean, and Chi-square tests were the statistical tools used to answer the problems posed in this study. Findings divulged after the transcription, teachers were only utilizing elicitation, explicit correction, recast, and repetition. Moreover, students perceived that elicitation oral error correction type is often used while explicit correction, recast, and repetition are only used sometimes by their English teachers.  Meanwhile, ELAS results indicate levels of language anxiety in the ESL classes and mainstream, although language anxiety is significantly higher in ESL classes. As to correlation, it was found out that the rate of occurrence of explicit correction, recast, and repetition as perceived by ESL English major students of their English teachers’ oral error correction types have no significant relationships to their English language anxiety. This study suggests that oral error correction has nothing to do with the English language anxiety of English major students and that English teachers shall retain the practice of the oral error correction for it does not give high level of learners’ anxiety in learning English.